Selected works of D. T. Suzuki - Suzuki, Daisetz Teitaro (University of California Press, 2015)
Daisetsu Teitaro Suzuki's writings introduced Buddhism to much of the world outside Asia. The second volume, Pure Land, presents ten writings on Pure Land Buddhism. In his writings, Suzuki highlights certain themes in Pure Land Buddhism and deemphasizes others, shifting focus from a future goal to a present religious experience wherein one realizes the nonduality between the Buddha and oneself and between paradise and this world.